A prospective study of post-cesarean delivery hypoxia after spinal anesthesia with intrathecal morphine 150 μg. (November 2017) - Ladha, Karim S.; Kato, Rie; Tsen, Lawrence C.; Bateman, Brian T.; Okutomi, Toshiyuki
Highlights: In this study, mild desaturation after 150 μg intrathecal morphine was common. Desaturation occurred most frequently 4–8 hours after intrathecal morphine. Obesity and a positive Berlin questionnaire were predictive of mild desaturation. Abstract: Introduction: Delayed respiratory depression is a feared complication of intrathecal morphine in patients undergoing cesarean delivery. The incidence, timing and risk factors for hypoxia in this population are not known. Methods: Patients undergoing cesarean delivery under spinal anesthesia at a tertiary care center from October 2012 to March 2016 were included in the study. The Berlin sleep apnea Questionnaire was completed before surgery. Oxygen saturation was recorded every second for 24 hours after the initiation of spinal anesthesia. Desaturation events were defined as a median saturation of <90% (mild) or <85% (severe) across a 30-s period. Multivariable logistic regression was used to determine predictors of a desaturation event. Results: A total of 721 patients were included in the analysis. Within this cohort, 169 women (23%) experienced at least one mild desaturation event, 91 (13%) experienced two or more mild desaturations, and 26 (4%) suffered a severe desaturation event. After the administration of intrathecal morphine, the median times to first mild or first severe desaturation were 7.4 (IQR 4.1–13.5) h and 12.0 (IQR 5.4–19.6) h, respectively. Patients who screened positive for sleep apnea had increased odds of having a mild desaturation event (OR 2.31, 95% CI 1.40 to 3.79, P =0.001), as did patients who were obese (OR 1.80, 95% CI 1.05 to 3.09, P =0.033). Conclusions: Mild hypoxemia occurred frequently in women receiving intrathecal morphine 150 μg for post-cesarean analgesia. Desaturations were observed most frequently 4–8 hours after administration of intrathecal morphine. Obesity and a positive Berlin Questionnaire were risk factors for hypoxemic events.